2014
DOI: 10.2174/13816128113199990029
|View full text |Cite
|
Sign up to set email alerts
|

CDK Inhibitors Induce Mitochondria-mediated Apoptosis Through the Activation of Polyamine Catabolic Pathway in LNCaP, DU145 and PC3 Prostate Cancer Cells

Abstract: Androgen signaling is critical in prostate cancer development and progression. The co-existence of hormone responsive and irresponsive cells due to functional androgen receptor (AR) in prostate gland is the major obstacle in prostate cancer therapy models. Targeting aberrant cell cycle by novel cell cycle blocking agents is a promising strategy to treat various types of malignancies. Purvalanol and roscovitine are cyclin dependent kinase (CDK) inhibitors able to activate apoptotic cell death by inducing cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…It was reported that CDK inhibitors could activate caspasedependent apoptosis by altering mitochondria membrane functions in various cancer cell lines such as breast, prostate, lung, and colon cancer cells [6,8,28]. Bax is an essential key molecule in the caspasedependent mitochondrial activated apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that CDK inhibitors could activate caspasedependent apoptosis by altering mitochondria membrane functions in various cancer cell lines such as breast, prostate, lung, and colon cancer cells [6,8,28]. Bax is an essential key molecule in the caspasedependent mitochondrial activated apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Roscovitine and purvalanol, novel CDK inhibitors, are referred as strong apoptotic inducers, which prevent the binding efficiency of CDKs to their cyclin partners. Therefore, these drugs effectively induced cell cycle arrest and apoptosis in prostate [8], breast [9], lung [10], cervix [11] and colon cancer [12,13] cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to WST-1 assay, PC-3 cells were more sensitive against torulene treatment compared to LNCaP cells. 18,27 Cell morphology plays vital roles in diverse cellular processes, including cell growth, motility, proliferation, and division. 21 To investigate the mechanism induced by the carotenoids, the changes in cell morphology were also observed and the observation results were consistent with that of viability analysis.…”
mentioning
confidence: 99%
“…27,28 The decrease in MMP is the earliest intracellular event before the apoptosis caused by the mitochondria-mediated death pathway, so the decline of MMP is considered as a symbolic event of early cellular apoptosis. 16 In this assay, both groups showed a significant (p < 0.05) decrease in MMP when treated with carotenoids compared to the control group.…”
mentioning
confidence: 99%
“…Another proposed mechanism of control—as suggested by epidemiological studies in colorectal cancer patients (Seiler, 2003; Laukaitis and Gerner, 2011)—is the induction of polyamine catabolism and subsequent regulation of cell proliferation and cancer progression (Arisan et al, 2014). Polyamines are small cationic molecules, formed from the decarboxylation products of ornithine and S-adenosyl-methionine.…”
Section: Aspirin and Cox-independent Regulation Of The Cell Cycle In mentioning
confidence: 99%